Atezolizumab in Patients with Metastatic Urothelial Carcinoma Who Have Progressed After First-line Chemotherapy: Results of Real-life Experiences - KÖSTEK, OSMAN; BAŞOĞLU TÜYLÜ, TUĞBA (ELSEVIER, 2021)
Background: Atezolizumab (ATZ) has demonstrated antitumor activity and manageable safety in previous studies in patients with locally advanced or metastatic platinum resistant urothelial carcinoma. Objective: To compare the real-life experience and data of clinical trials on ATZ treatment in metastatic urothelial carcinoma. Design, setting, and participants: Patients with urothelial cancer treated with ATZ after progression on first-line chemotherapy from an expanded access program were retrospectively studied. Data of patients were obtained from their files and hospital records. Safety was evaluated for patients treated with at least one cycle of ATZ. Outcome measurements and statistical analysis: The primary endpoint was objective response rate (ORR). The secondary endpoints are overall survival (OS), progression-free survival (PFS), duration of response, and safety profile of patients. Kaplan-Meier methods were used to calculate median follow-up and estimate PFS and OS. Results and limitations: Data of 115 enrolled patients were analyzed. Most of the patients (92.3%, n = 106) had received chemotherapy regimen only once prior to ATZ. The median follow-up duration was 23.5 mo. The complete response rate, partial response rate, and ORR were 8.7% (n = 10), 20.0% (n = 23), and 28.7% (n = 33), respectively. The median duration of response was 20.4 mo (95% confidence interval [CI], 6.47-28.8). Of the 33 patients who responded to treatment, 60% (n = 20) had an ongoing response at the time of the analysis. PFS and OS with ATZ were 3.8 mo (95% CI, 2.25-5.49) and 9.8 mo (95% CI, 6.7-12.9), respectively. All-cause and any-grade adverse events were observed in 113 (98%) patients. Of the patients, 64% experienced a treatment-related adverse event of any grade and 24 (21.2%) had a grade 3-4 treatment-related adverse event. Limitations of the study included its retrospective design, and determination of treat-ment response based on clinical notes and local radiographic studies. Conclusions: In these real-life data, ATZ was effective and well tolerated in patients with metastatic urothelial carcinoma who have progressed with platinum-based first-line chemotherapy. ATZ is an effective and tolerable treatment for patients with locally advanced or metastatic platinum-resistant urothelial carcinoma in our study, similar to previously reported trials. Patient summary: Atezolizumab is effective and well-tolerated in patients with meta-static urothelial cancer who progressed with first-line chemotherapy, consistent with the outcomes of the previous clinical trials in this setting. (c) 2020 European Association of Urology. Published by Elsevier B.V. All rights reserved.
Keywords: Atezolizumab; Urothelial carcinoma; Bladder cancer; Immunotherapy; TRIAL; MULTICENTER; CISPLATIN; SURVIVAL; THERAPY; PLUS